Concept and theoretical framework of multidimensional health poverty: a bibliometrics analysis - Ye LI; Qunhong WU; Yongqiang LAI; Mingli JIAO; Xinwei LIU; Linghan SHAN (Editorial Office of Chinese Journal of Public Health, 2023)
The negative overlap and cycle between disease and poverty outcomes and burdens have become a core driver of existing poverty in China, and constitute an essential characteristic factor of health poverty. Compared to economic and cultural poverty, health poverty has become a key constraint in the fight against poverty, and an important risk and challenge in sustaining China's achievements in the post-poverty reduction era. With bibliometrics method, qualitative expert interview and using social network analysis, we define and explain the connotation and characteristics of multidimensional health poverty from multiple perspectives of disease, economy, culture and education, and governance system; we also try to construct a theoretical model of health poverty involving three dimensions: health capacity, health right, and health risk and deconstruct the action mechanisms of the three aspects in the occurrence, expansion, continuation, and elimination of health poverty.